Terapi ARV pada Penderita Ko-Infeksi TB-HIV: [Antiretroviral Therapy in TB-HIV Co-Infection Patient] - Indana Eva Ajmala; Laksmi Wulandari (Faculty of Medicine Universitas Airlangga, 2015)
TB and HIV have a very close relationship since the development of AIDS. Through a significant reduction in cellular immunity, HIV affects the pathogenesis of tuberculosis, thereby increasing the risk of TB in HIV co-infected individuals. In 2006, there were an estimated 9.2 million new TB cases worldwide, there were 710.00 in patients with HIV and 500,000 cases with MDR-TB. Sensitivity to TB associated with cytokine production by T lymphocytes (IFN gamma and TNF are like alpha). During HIV infection, IFN gamma production declined dramatically in line with the decrease in CD4 T lymphocytes This leads to an increased risk of developing reactivation or reinfection Mycobacterium tuberculosis. Clinical symptoms of pulmonary TB in people living with HIV are often non-specific. Clinical symptoms often found are fever and significant weight loss. The other symptoms usually associated with extrapulmonary TB. Antiretrovirals are drugs that inhibit HIV replication. The main priority in patients co-infected with TB-HIV is a start of TB therapy, followed by cotrimoxazole and ARV. ARV treatment recommendation on co-infection tuberculosis is starting ARV therapy to all people living with HIV with active TB, regardless of CD4 cell count. Antiretroviral therapy start as soon as possible after TB treatment can be tolerated, as soon as 2 weeks and no more than 8 weeks. Regimen set by WHO for first-line regimen containing two nucleoside reverse transcriptase inhibitors (NRTIs) plus one non-nucleoside reverse transcriptase inhibitors (NNRTIs). In the co-infection of TB-HIV nucleoside was elected WHO recommended Zidovudine (AZT) or tenofovir disoproxil fumarate (TDF), in combination with lamivudine (3TC) or emricitabine (FTC). For NNRTI, WHO recommends efavirenz (EFV) or nevirapine (NVP).